Revisiting note-taking strategies for mathematics during online classes / Muniroh Binti Hamat, Jamal Othman and Rofiza Aboo Bakar - Hamat, Muniroh; Othman, Jamal; Aboo Bakar, Rofiza (Unit Penulisan Dan Penerbitan JSKM, 2022)
Teaching and learning have been done entirely online for the past two years because of the Covid-19 pandemic. Therefore, students should be aware of the good methods for taking notes in class as the ability in doing so will help them grasp important content well. In turn, reading and revising will be made much easier when they need to only refer to their notes which are simple yet complete with important details. The ability to take notes and write them in a way that corresponds with each lecturer’s presentation is an art that should be learnt by all students. However, taking notes is sometimes overlooked by many, especially in mathematics. Thus, students should be informed of note-taking strategies and what to address in and review the materials that they need to read. This article aims to share with students some note-taking strategies that may serve as a guide in helping students improve their performance especially in mathematics